2007
DOI: 10.1021/jo0702490
|View full text |Cite
|
Sign up to set email alerts
|

Triptycene-Based Expanded Oxacalixarenes:  Synthesis, Structure, and Tubular Assemblies in the Solid State

Abstract: Owing to the unique 3D rigid structure of triptycene, two novel expanded oxacalixarenes 5a and 5b as a pair of diastereomers were efficiently synthesized in a single step by the SNAr reaction of 2,7-dihydroxytriptycene with 2,3,5,6-tetrachloropyridine in the presence of cesium carbonate. Similarly, two pairs of other triptycene-based expanded oxaxalixaenes 7a,7b and 9a,9b could also be obtained by the SNAr reactions of 2,7-dihydroxytriptycene with 1,5-difluoro-2,4-dinitrobenzene and cyanuric chloride, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 24 publications
0
59
0
Order By: Relevance
“…Chen and coworkers introduced triptycene units into the heterocalix[4]-aromatic system, which resulted in several new triptycenecontaining heterocalix [4]aromatics with enlarged cavities and fixed conformations, and found that this class of heterocalix [4]aromatic compounds could encapsulate a number of different guest species. [7] In the second strategy, more aromatic rings are introduced into the heterocalix[4]aromatic scaffolds. In this regard, several larger heterocalix[n]-aromatics [n Ͼ 4] have been constructed [4m,8] and the guest complexation behaviour of some larger heterocalix[n]aromatics [n Ͼ 4] have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and coworkers introduced triptycene units into the heterocalix[4]-aromatic system, which resulted in several new triptycenecontaining heterocalix [4]aromatics with enlarged cavities and fixed conformations, and found that this class of heterocalix [4]aromatic compounds could encapsulate a number of different guest species. [7] In the second strategy, more aromatic rings are introduced into the heterocalix[4]aromatic scaffolds. In this regard, several larger heterocalix[n]-aromatics [n Ͼ 4] have been constructed [4m,8] and the guest complexation behaviour of some larger heterocalix[n]aromatics [n Ͼ 4] have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…When the amounts of dichloro(methoxy)methane and aluminum chloride were increased further, a pair of triformyltriptycene isomers was obtained. Treatment of triptycene (1) with 15 equivalents of dichloro(methoxy)methane in the presence of 15 equivalents of aluminum chloride gave 2,6,14-triformyltriptycene (26) and 2,7,14-triformyltriptycene (27) in 65% and 20% yield, respectively (Scheme 11c).…”
Section: Account Syn Lettmentioning
confidence: 99%
“…Triazine macrocyclic compounds demonstrated high potential application in molecular recognition [14][15][16][17][18][19]. However, this did not refer to Schiff base containing macrocycles [20,21].…”
Section: Introductionmentioning
confidence: 99%